USING STORY COMPLETION TO INCREASE STUDENTS’ ABILITY IN SPEAKING SKILL AT MTS MARDHATILLAH - Agustiawati, Hartini; Berliani, Wulandari (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
Learning English as a foreign Language is challenging. It needs motivation and strong effort. The most difficult skill in English is Speaking. There are some components for making speaking improved. Those components must be covered and faced by all speakers. In order to teach Speaking skill to students, the teachers can use appropriate method which is effective and right for students’ need. Story completion can be the sollution to make students easy to speak and get ideas. Story Completion has been applied and the result showed that it was effective and helped students to write. Therefore, many methods can be applied to make students fun and happy in speaking. We can choose method which is effective and easily to be used. The purpsoe of this study is to know whether the story completion is effective or no to increase students’ ability in speaking skill. .Quantitative method with quasi experimental were used. The result of this study showed that there was siginificant improvement the use of story completion in speaking skill Pembelajaran Bahasa Inggris sebagai Bahasa asing cukup menantang. Sehingga membutuhkan semangat dan motivasi yang kuat karena berbicara Bahasa inggris merupakan keahlian yang sulit. Ada beberapa komponen dalam membuat kemampuan Bahasa Inggris meningkat. Untuk mengajarkan berbicara Bahasa Inggris kepada siswa membutuhkan metode yang tepat yang efektif dan sesuai kebutuhan siswa. Story completion adalah salah satu solusi untuk berbicara Bahasa Inggris . Story completion dapat membuat pembelajaran speaking menjadi menyenangkan. Tujuan dari penelitian ini untuk mengetahui apakah efektif atau tidak dalam penggunaan story completion pada keahlian berbicara Bahasa Inggris. Kuantitatif eksperimental telah dipakai. Dan hasilnya terdapat peningkatan yang signifikan pada penggunaan Story completion dalam Keahlian Berbicara Bahasa Inggris siswa.